Distributed Multiple Tuned Mass Dampers for Wind Response Control of Chimney with Flexible Foundation. (2017) - Elias, Said; Matsagar, Vasant; Datta, T.K.
Abstract: Multi-mode wind response control of chimneys on flexible foundation is studied. The multi-mode control is achieved using distributed multiple tuned mass dampers (d-MTMDs). A reinforced concrete (RC) chimney is considered as an assemblage of beam elements, each assumed to have constant diameter over the element length, and soil-structure interaction (SSI) is duly accounted for. The soil is idealized in single strata beneath the foundation, which consist of annular raft foundation having the internal and external diameter 15 m and 40 m, respectively and having depth of 2.5 m. The raft and the surrounding soil are modeled considering frequency independent constants for the springs and dashpots. The time domain wind analysis based on Newmark's method of average acceleration is employed for the non-classically damped system. The performance of the d-MTMDs is compared with the case of single tuned mass damper (STMD), d-MTMDs controlling the fundamental modal responses (d-MTMDs-1), and arbitrarily installed distributed MTMDs (ad-MTMDs). The displacement and acceleration response at the top of the chimney under wind forces are computed to study the effectiveness in the STMD, d-MTMDs-1, ad-MTMDs, and d-MTMDs cases. It is concluded that the d-MTMDs are more effective than the STMD, d-MTMDs-1, and ad-MTMDs, while considering equal total mass of the TMD(s). Furthermore, the soil type greatly affects the design parameters of the STMD/ d-MTMDs-1/ ad-MTMDs/ d-MTMDs, and wind response of the chimney with flexible foundation.